2020
DOI: 10.1080/26895293.2020.1819444
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of microwave ablation and entecavir as a combination treatment for primary liver cancer and their effects on hepatitis B virus and liver function

Abstract: Xie (2020) Efficacy of microwave ablation and entecavir as a combination treatment for primary liver cancer and their effects on hepatitis B virus and liver function,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…During MWA, microwaves produce heat that destroys tumor cells and creates thermal coagulation and localized tissue necrosis. The alternating electric field forces polar molecules in tissue, primarily water molecules, to continuously realign with the oscillating electric field leading to heat generation and, hence, increase of the temperature of the tissue [16]. Thermal destruction of the tissue depends not only on the type of the tissue but also on the distance from the antenna, the quantity of the delivered energy and the length of the treatment [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During MWA, microwaves produce heat that destroys tumor cells and creates thermal coagulation and localized tissue necrosis. The alternating electric field forces polar molecules in tissue, primarily water molecules, to continuously realign with the oscillating electric field leading to heat generation and, hence, increase of the temperature of the tissue [16]. Thermal destruction of the tissue depends not only on the type of the tissue but also on the distance from the antenna, the quantity of the delivered energy and the length of the treatment [16].…”
mentioning
confidence: 99%
“…The alternating electric field forces polar molecules in tissue, primarily water molecules, to continuously realign with the oscillating electric field leading to heat generation and, hence, increase of the temperature of the tissue [16]. Thermal destruction of the tissue depends not only on the type of the tissue but also on the distance from the antenna, the quantity of the delivered energy and the length of the treatment [16]. Since the radiation efficiency of an antenna depends on matching the frequency with water molecule resonance, it was shown that the system operating at 2.45 GHz is very efficient producing greater power deposition and larger ablations in a shorter time [17].…”
mentioning
confidence: 99%